(untitled) (Clinics, 2023)
Objective: Amygdala has been demonstrated as one of the brain sites involved in the control of cardiorespiratory functioning. The structural and physiological alterations induced by epileptic activity are also present in the amygdala and reflect functional changes that may be directly associated with a sudden unexpected death. Seizures are always associated with neuronal damage and changes in the expression of cation-chloride cotransporters and Na/K pumps. In this study, the authors aimed to investigate if these changes are present in the amygdala after induction of status epilepticus with pilocarpine, which may be directly correlated with Sudden Unexpected Death in Epilepsy (SUDEP). Methods: Pilocarpine-treated wistar rats 60 days after Status Epilepticus (SE) were compared with control rats. Amygdala nuclei of brain slices immunostained for NKCC1, KCC2 and α1-Na+/K+-ATPase, were quantified by optical densitometry. Results: The amygdaloid complex of the animals submitted to SE had no significant difference in the NKCC1 immunoreactivity, but KCC2 immunoreactivity reduced drastically in the peri-somatic sites and in the dendritic-like processes. The α1-Na+/K+-ATPase peri-somatic immunoreactivity was intense in the rats submitted to pilocarpine SE when compared with control rats. The pilocarpine SE also promoted intense GFAP staining, specifically in the basolateral and baso-medial nuclei with astrogliosis and cellular debris deposition. Interpretation: The findings revealed that SE induces lesion changes in the expression of KCC2 and α1-Na+/K+-ATPase meaning intense change in the chloride regulation in the amygdaloid complex. These changes may contribute to cardiorespiratory dysfunction leading to SUDEP.